2022
DOI: 10.3390/s22093539
|View full text |Cite
|
Sign up to set email alerts
|

Technological Requirements and Challenges in Wireless Body Area Networks for Health Monitoring: A Comprehensive Survey

Abstract: With the rapid growth in healthcare demand, an emergent, novel technology called wireless body area networks (WBANs) have become promising and have been widely used in the field of human health monitoring. A WBAN can collect human physical parameters through the medical sensors in or around the patient’s body to realize real-time continuous remote monitoring. Compared to other wireless transmission technologies, a WBAN has more stringent technical requirements and challenges in terms of power efficiency, secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 142 publications
0
38
0
Order By: Relevance
“…A data scheduling approach for monitoring inter-Wireless Body Area Network (WBAN) systems was developed in [18] to meet the Quality of Service (QoS) requirements in Wireless Body Area Network (WBAN) networks. The authors proposed using a critical delay parameter to prioritize and group packets into an aggregated frame for transmission to the medical server.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A data scheduling approach for monitoring inter-Wireless Body Area Network (WBAN) systems was developed in [18] to meet the Quality of Service (QoS) requirements in Wireless Body Area Network (WBAN) networks. The authors proposed using a critical delay parameter to prioritize and group packets into an aggregated frame for transmission to the medical server.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 6 illustrates the mean slowdown of delay-tolerant short packets under the EDF, Priority EDF and PS scheduling schemes, where short packets have sizes of less than or equal to x s = 75 Kilobytes. To obtain this figure, expressions (12), (14) and (18) were used. It can be observed that, at both low system load values of 𝜌 = 0.5 and high system loads of 𝜌 = 0.9, the PS scheme outperforms the EDF and Priority EDF schemes for delay-tolerant short packets.…”
Section: Evaluation Of the Mean Slowdown Of Packet Sizes For Delay To...mentioning
confidence: 99%
“…Although the need of energy conservation after implementing security was addressed in this study piece, full energy conservation strategies were not offered. The needs and difficulties of the WBAN were thoroughly and in‐depth investigated by the researchers in Reference 19. They started by thoroughly examining WBAN applications before concentrating on the WBAN's criteria and difficulties.…”
Section: Related Studymentioning
confidence: 99%
“…WBANs can be categorized into three tiers of level communication: Intra-WBAN, inter-WBAN, and beyond-WBAN communications [5]. Tier-1 is intra-WBAN communication, consisting of a set of sensors placed on or implanted into the human body.…”
Section: Introductionmentioning
confidence: 99%